2020
DOI: 10.4028/www.scientific.net/kem.858.193
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Geopolymer Mortar Subjected to High Temperature

Abstract: Geopolymer concrete was presented to produce alternative binder to cement. This study considered the influence of silica fume on the properties of metakaolin based geopolymer mortar exposed to high temperature up to 800 °C. Five mortar mixes were used with silica fume replacing level of 0, 10, 20, 30 and 40% of weight of metakaolin. The results demonstrated that the compressive and splitting tensile strength increased with increasing the silica fume replacing level up to 40% of weight of metakaolin for all bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…This caused voids in the sample and adversely affected the mechanical properties of the samples. Ibrahim et al 51 stated that there was a decrease in the strength of metakaolin‐based geopolymer mortars containing SF exposed to 800°C.…”
Section: Resultsmentioning
confidence: 99%
“…This caused voids in the sample and adversely affected the mechanical properties of the samples. Ibrahim et al 51 stated that there was a decrease in the strength of metakaolin‐based geopolymer mortars containing SF exposed to 800°C.…”
Section: Resultsmentioning
confidence: 99%
“…From the analysis of the influencing factors of compressive strength in the previous chapter, the tensile strength performance can be analogously applied. Lbrahim [27] studied the cleavage tensile strength of GC under two variables of SF substitution rate and temperature based on orthogonal experiments. These data revealed the splitting tensile strength of GC is within 400°C, which increases with the increase of combustion temperature, and the downward trend is shown between 400°C and 800°C.…”
Section: Tensile Strengthmentioning
confidence: 99%
“…Ali et al [11] proposed that the compressive strength and flexural strength of geopolymer showed a tendency to increase and then decrease with the increase of combustion temperature, and reached the highest point at 400℃. Whereas, Payakaniti [12] found that the compressive strength of geopolymer reached its maximum after exposure to 200℃.…”
Section: Introductionmentioning
confidence: 99%